(untitled) (Journal of Engineering, 2026)
This study aims to investigate the effect of different curing methods on the strength of reactive powder concrete (RPC) and to evaluate the use of brick powder as a partial replacement of cement. The use of brick powder is intended to reduce cement content and utilize construction waste more sustainably. In this work, waste clay bricks collected from construction sites were crushed into fine powder and used at replacement levels of 5% and 10%. The mixtures were subjected to different curing methods, including standard curing (C.S), coating curing, and warm water curing, followed by standard curing. The warm curing included immersion in water at (35 ± 2) °C for one day (W1S), two days (W2S), and three days (W3S), followed by standard curing until testing. The results showed that the compressive strength of the control mix under standard curing reached 92.5 MPa at 28 days. The strength increased by 11.24%, 21.72%, 25.08%, and 29.83% for (C.S), (W1S), (W2S), and W3S, respectively. In addition, the mixture with 10% brick powder showed better performance, with increases of 30.94%, 31.89%, and 32.77% in compressive strength, 29.03%, 29.60%, and 30.50% in flexural strength, and 27.80%, 28.89%, and 29.99% in tensile strength at 7, 28, and 90 days, respectively, compared to the control mix. Overall, the results suggest that brick powder can be used as a sustainable material in RPC, especially when combined with suitable curing methods.